Development of a robust hydroponic method for screening of sunflower (Helianthus annuus L.) accessions for tolerance to heat and osmotic stress - Muhammad Shehzad (Nature Portfolio, 2021)
Abstract Hydroponic systems are known to provide a platform for uniform growth conditions until the reproductive stage. However, many plant species, including sunflower, show poor growth and survivability under conventional hydroponic systems due to poor nutrient availability, hypoxia and algal contamination. Thus, we tested various hydroponic systems to select a hydroponic system suitable for screening of sunflower germplasm. Sunflower accessions showed better growth and leaf gas exchange in newly-designed over conventional hydroponic systems. Selected hydroponic systems were further engaged in sunflower accession screening under heat and osmotic stress in a two-pan system (210 cm × 60 cm). Heat stress treatment was applied by growing sunflower germplasm at 42 °C and osmotic stress by adding polyethylene glycol 8000 which decreased the osmotic potential to − 0.6 MPa. There was significant variability among the sunflower accessions for their ability to survive under stress. Accessions such as C-2721 (43%), C-291 (46%) and D-14 (43%) had lower cell membrane injury percentage under osmotic stress and high seedling survivability (60‒80%) under heat stress when compared with susceptible accessions. Moreover, resistant accessions exhibited greater cuticular waxes and root length but lower transpiration losses. The newly designed hydroponic platform proved reliable for the selection of resistant sunflower accessions. Selected parental lines were validated by assessing their hybrids under field trials across two seasons under water and temperature stress during the reproductive phase (autumn). Hybrid H3 obtained by crossing drought and heat resistant parents had the highest seed yield and water use efficiency.